1952
DOI: 10.1139/v52-067
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence Phenomena in the Critical Region: I. The Gravity Effect in Ethane From Light Scattering

Abstract: A method of measuring density gradients caused by gravitational compression in gases near the critical region is described. Relative light scattering coefficients of ethane in bombs 40 cm. long increase, remain constant, or decrease in the downward direction, depending upon the mean filling density. These observations have been correlated with the variation of scattering coefficient with density, and show that appreciable density gradier~ts exist. These observations are confirmed by parallel studies of condens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1953
1953
1975
1975

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In previous publications (3,4), the authors reported large vertical gradients in density near the liquid-vapor critical point in one-component systems. These gradients, due t o gravitational compression, were anticipated owing to the large compressibility of a fluid in the critical region.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…In previous publications (3,4), the authors reported large vertical gradients in density near the liquid-vapor critical point in one-component systems. These gradients, due t o gravitational compression, were anticipated owing to the large compressibility of a fluid in the critical region.…”
Section: Introductionmentioning
confidence: 92%
“…The essential details of the apparatus have already been described (3,4). In the present experiments, only the methods of filling and changing the compositioi~ of the fluid were altered.…”
Section: Apparatz~smentioning
confidence: 99%
See 3 more Smart Citations